Best damn Cisco internetworking book period (Syngress, 2003)
Talks about various Cisco internetworking topics. This book provides an understanding of Cisco's VoIP solutions and the means to put them to work. It discusses IPv6 Protocols, as well as IP Quality of Service (QoS) and shows how it applies to Enterprise and Internet Service Provider (ISP) environments. It also covers Cisco wireless technologies.